Analyzing the rhetoric of contemporary BSMRSTU student movements: manifestations and social implications in Gopalganj, Bangladesh - Kalam, Abul; Al-Mamun, Md. (Frontiers in Political Science, 2024)
Background The rich tapestry of student politics and movements in Bangladesh is marked by a history of significant contributions to the country's sociopolitical landscape. This study was prompted by a keen interest in exploring the dynamics of contemporary student movements at Bangabandhu Sheikh Mujibur Rahman Science and Technology University (BSMRSTU), Gopalganj, and their interplay with the broader sociopolitical climate of Bangladesh. A critical examination of these movements reveals a complex web of motivations, strategies, and outcomes that both mirror and influence national sociopolitical dialogues. Methods Employing qualitative research methods, including in-depth interviews (IDI) with 26 individuals directly affected by the culture and mechanics of these movements, this study uncovers the nuanced ways in which student activism at BSMRSTU mobilizes cultural ideologies toward societal change. Purposive and snowball sampling techniques were utilized to select participants, revealing that the rhetoric of movements—framed around justice, rights, equality, and reform—plays a crucial role in recruiting and energizing participants. Results However, this investigation also highlights a darker facet of these movements: the destructive consequences of specific actions, such as property damage, which not only impact the immediate community but also fuel further unrest. The prevalence of movements centered on themes of injustice underscores the urgent need for both governmental and academic institutions to engage more constructively with student concerns. Addressing this gap requires a nuanced understanding of the motivations behind student movements and a commitment to implementing policies that nurture a culture of dialogue and reform. Conclusion This study, therefore, problematizes the contemporary student movements at BSMRSTU by questioning the balance between activism and the potential for unintended consequences, urging a reevaluation of how such movements are perceived and managed in the context of Bangladesh's evolving sociopolitical milieu. For harmful movement culture in academia to be prevented, government and university authorities must take student movements seriously and implement policies and strong norms.